ANALISIS MINAT BERWIRAUSAHA MELALUI IMPLEMENTASI DUA PERSPEKTIF TEORI (SCT x TPB) - Arimbawa, Putu Adi Putra; Putri, Leilani Ivana (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2023)
Entrepreneurs play a significant role in a country's development, particularly in its economic growth. Recognizing the importance of entrepreneurship, many countries, including Indonesia, have integrated entrepreneurial education into their school curriculum to equip students with fundamental entrepreneurial skills and knowledge. This implementation aims to foster students' entrepreneurial intention upon graduation. This study aims to investigate the impact of entrepreneurial education on students' entrepreneurial intention. To achieve this goal, we employ two theoretical frameworks: The Social Cognitive Theory (SCT) and The Theory of Planned Behavior (TPB). Both theories emphasize the role of self-efficacy as a key determinant of individual intention towards behavior. Additionally, TPB highlights the significance of perceived behavioral control in shaping individual intention. By utilizing Partial Least Square (PLS) analysis, we examine our proposed conceptual framework, which explores the relationship between entrepreneurial education and students' entrepreneurial intention. Our findings indicate that self-efficacy plays a crucial role in mediating the link between entrepreneurial education and entrepreneurial intention. However, we were unable to provide sufficient evidence to support the significant impact of perceived behavioral control on improving students' entrepreneurial intention. The results of this study hold both theoretical and practical implications, which will be thoroughly discussed.